Respuesta :

Answer:

20) [tex]\displaystyle [4, 1][/tex]

19) [tex]\displaystyle [-5, 1][/tex]

18) [tex]\displaystyle [3, 2][/tex]

17) [tex]\displaystyle [-2, 1][/tex]

16) [tex]\displaystyle [7, 6][/tex]

15) [tex]\displaystyle [-3, 2][/tex]

14) [tex]\displaystyle [-3, -2][/tex]

13) [tex]\displaystyle NO\:SOLUTION[/tex]

12) [tex]\displaystyle [-4, -1][/tex]

11) [tex]\displaystyle [7, -2][/tex]

Step-by-step explanation:

20) {−2x - y = −9

{5x - 2y = 18

[5x - 2y = 18]

{−2x - y = −9

{2x - ⅘y = 7 >> New Equation

___________

[tex]\displaystyle \frac{-1\frac{4}{5}y}{-1\frac{4}{5}} = \frac{-1\frac{4}{5}}{-1\frac{4}{5}}[/tex]

[tex]\displaystyle y = 1[/tex][Plug this back into both equations above to get the x-coordinate of 4]; [tex]\displaystyle 4 = x[/tex]

________________________________________________________________________________________

19) {−5x - 8y = 17

{2x - 7y = −17

[−5x - 8y = 17]

{4⅜x + 7y = 14 >> New Equation

{2x - 7y = −17

_____________

[tex]\displaystyle \frac{6\frac{3}{8}x}{6\frac{3}{8}} = \frac{-31\frac{7}{8}}{6\frac{3}{8}}[/tex]

[tex]\displaystyle x = -5[/tex][Plug this back into both equations above to get the y-coordinate of 1]; [tex]\displaystyle 1 = y[/tex]

________________________________________________________________________________________

18) {−2x + 6y = 6

{−7x + 8y = −5

¾[−7x + 8y = −5]

{−2x + 6y = 6

{5¼x - 6y = 3¾ >> New Equation

____________

[tex]\displaystyle \frac{3\frac{1}{4}x}{3\frac{1}{4}} = \frac{9\frac{3}{4}}{3\frac{1}{4}}[/tex]

[tex]\displaystyle x = 3[/tex][Plug this back into both equations above to get the y-coordinate of 2]; [tex]\displaystyle 2 = y[/tex]

________________________________________________________________________________________

17) {−3x - 4y = 2

{3x + 3y = −3

_________

[tex]\displaystyle \frac{-y}{-1} = \frac{-1}{-1}[/tex]

[tex]\displaystyle y = 1[/tex][Plug this back into both equations above to get the x-coordinate of −2]; [tex]\displaystyle -2 = x[/tex]

________________________________________________________________________________________

16) {2x + y = 20

{6x - 5y = 12

[6x - 5y = 12]

{2x + y = 20

{2x + 1⅔y = 4 >> New Equation

____________

[tex]\displaystyle \frac{2\frac{2}{3}y}{2\frac{2}{3}} = \frac{16}{2\frac{2}{3}}[/tex]

[tex]\displaystyle y = 6[/tex][Plug this back into both equations above to get the x-coordinate of 7]; [tex]\displaystyle 7 = x[/tex]

________________________________________________________________________________________

15) {6x + 6y = −6

{5x + y = −13

[6x + 6y = −6]

{5x - 5y = 5 >> New Equation

{5x + y = −13

_________

[tex]\displaystyle \frac{-4y}{-4} = \frac{-8}{-4}[/tex]

[tex]\displaystyle y = 2[/tex][Plug this back into both equations above to get the x-coordinate of −3]; [tex]\displaystyle -3 = x[/tex]

________________________________________________________________________________________

14) {−3x + 3y = 3

{−5x + y = 13

[−3x + 3y = 3]

{x - y = 1 >> New Equation

{−5x + y = 13

_________

[tex]\displaystyle \frac{-4x}{-4} = \frac{12}{-4}[/tex]

[tex]\displaystyle x = -3[/tex][Plug this back into both equations above to get the y-coordinate of −2]; [tex]\displaystyle -2 = y[/tex]

________________________________________________________________________________________

13) {−3x + 3y = 4

{−x + y = 3

[−3x + 3y = 4]

{x - y = 1 >> New Equation

{−x + y = 3

________

[tex]\displaystyle 1\frac{2}{3} ≠ 0; NO\:SOLUTION[/tex]

________________________________________________________________________________________

12) {−3x - 8y = 20

{−5x + y = 19

[−3x - 8y = 20]

{⅜x - y = 2½ >> New Equation

{−5x + y = 19

__________

[tex]\displaystyle \frac{-5\frac{3}{8}x}{-5\frac{3}{8}} = \frac{21\frac{1}{2}}{-5\frac{3}{8}}[/tex]

[tex]\displaystyle x = -4[/tex][Plug this back into both equations above to get the y-coordinate of −1]; [tex]\displaystyle -1 = y[/tex]

________________________________________________________________________________________

11) {x + 3y = 1

{−3x - 3y = −15

___________

[tex]\displaystyle \frac{-2x}{-2} = \frac{-14}{-2}[/tex]

[tex]\displaystyle x = 7[/tex][Plug this back into both equations above to get the y-coordinate of −2]; [tex]\displaystyle -2 = y[/tex]

I am delighted to assist you anytime my friend!